The sociocultural perspectives of the coronavirus pandemic - Kandasamy, Vishnu (Université d'Ottawa | University of Ottawa, 2023)
This Major Research Paper (MRP) seeks to showcase the value of sociological insight in analyzing medical phenomena such as the coronavirus pandemic. By adopting the social constructionist framework, the paper will examine the pandemic as a sociocultural issue to contribute to established sociological knowledge regarding pandemics. This examination will have two parts: the first focuses on understanding the pandemic as a sociocultural phenomenon and will focus on medical data through the lens of social and non-medical perceptions. The second focuses on how sociocultural perspectives impact the effectiveness of health measures by understanding the stigma surrounding the coronavirus and the non-medical factors that shape the reception of health measures. Through analyzing these sociocultural perspectives, the paper seeks to understand the benefit of understanding the social aspect of health and medicine and speculate what form a refined approach to the pandemic may take.